Evidence of thermophilic waste decomposition at a landfill exhibiting elevated temperature regions. (1st April 2021) - De la Cruz, Florentino B.; Cheng, Qiwen; Call, Douglas F.; Barlaz, Morton A.
Highlights: The estimated temperature limit for methane production in a landfill was 72 °C. Temperature inhibition was manifested in both methane yield and production rate. Genus Methanothermobacter likely played a key role in methane production. Microbial diversity did not change after temperature perturbations. Abstract: There have been several reports of landfills exhibiting temperatures as high as 80 to 100 °C. This observation has motivated researchers to understand the causes of the elevated temperatures and to develop predictive models of landfill temperature. The objective of this research was to characterize the methanogenic activity of microbial communities that were derived from landfill samples excavated from a section of a landfill exhibiting gas well temperatures above 55 °C. Specific objectives were to: (1) determine the upper temperature limit for methane production; (2) evaluate the kinetics of methane generation when landfill-derived microcosms are incubated above and below their excavation temperature and derive a temperature inhibition function; and (3) evaluate microbial community shifts in response to temperature perturbations. Landfill microcosms were derived from 57 excavated landfill samples and incubated within ± 2.5 °C of their excavation temperature between 42.5 °C and 87.5 °C. Results showed an optimum temperature for methane generation of ~57 °C and a 95% reduction in methane yield at ~72 °C. When select cultures were perturbed between 5 °C below and 15 °C above their in-situ temperature, both the rate and maximum methane production decreased as incubation temperature increased. Microbial community characterization using 16S rRNA amplicon sequencing suggests that thermophilic methanogenic activity can be attributed to methanogens of the genus Methanothermobacter . This study demonstrated that from a microbiological standpoint, landfills may maintain active methanogenic processes while experiencing temperatures in the thermophilic regime (<72 °C).